ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT KECELAKAAN KERJA PADA KARYAWAN PABRIK TAHU KHARISMA - Corneta, Dwindy Rizki; Zetli, Sri (LPPM Universitas Putera Batam, 2021)
The purpose of this study is to look at the factors that impact the rate of work accidents among Tofu Kharisma Factory employees. Three independent variables, namely technical, human, and environmental factors, and one dependent variable, work accidents, are used in this study. Multiple linear regression was utilized in this research. This study's premise is that technological, human, and environmental factors all have a major impact on employee workplace accidents. Then there's a partial effect, with human factors influencing work accidents, technical aspects influencing work accidents, and environmental elements influencing work accidents. The following findings are derived based on the calculation results. employee accidents are influenced by a combination of technological, human, and work environment variables. Furthermore, employee work accidents are influenced by a combination of human, technological, and environmental variables.